2024
DOI: 10.1037/pag0000793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and word frequency on Korean visual word recognition: Evidence from a web-based large-scale lexical-decision task.

Hyunah Baek,
Peter C. Gordon,
Wonil Choi

Abstract: The present study examined age differences in word-frequency effects in Korean visual word recognition through a large-scale, web-based lexical-decision task. Four hundred ninety-seven adult Korean speakers in their 20s through 60s participated in the task, in which they decided the lexicality of 120 Korean words varying in frequency and 120 nonwords. Overall, both lexical-decision accuracy and response times increased with age, and more frequent words were recognized more rapidly than less frequent words. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…These findings are significant in suggesting age constancy in word recognition from the surface form even under challenging perceptual conditions. Baek et al (2024) also demonstrated age-related stability in visual word recognition, as measured by word frequency effects in Korean speakers. Using a lexical decision task with almost 500 adults in their 20s through 60s, they showed that higher frequency Korean words were recognized more quickly than lower frequency words, similar to the well-established effect that has been shown with English words.…”
Section: How Aging Impacts Language Mechanismsmentioning
confidence: 77%
“…These findings are significant in suggesting age constancy in word recognition from the surface form even under challenging perceptual conditions. Baek et al (2024) also demonstrated age-related stability in visual word recognition, as measured by word frequency effects in Korean speakers. Using a lexical decision task with almost 500 adults in their 20s through 60s, they showed that higher frequency Korean words were recognized more quickly than lower frequency words, similar to the well-established effect that has been shown with English words.…”
Section: How Aging Impacts Language Mechanismsmentioning
confidence: 77%